Talking Stick-Based Team Games Tournament Learning Model on Students' Interest in Learning Akidah Akhlak - Siti Umi Kholifah; Deden Makbuloh; M. Indra Saputra (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This research is driven by the low interest of students in the subject of Aqidah Akhlak at MTs Darul Huda Bandar Lampung, specifically characterized by minimal engagement and attention. Preliminary findings indicated that while students experienced feelings of enjoyment, their enthusiasm did not translate into active participation or optimal learning focus. This study aims to determine the effect of the Talking Stick-based Team Games Tournament (TGT) learning model on students' learning interests. The research involved class VIII D as the experimental group and class VIII C as the control group, using a quantitative quasi-experimental approach with a post-test-only control group design. The results of the independent sample t-test yielded a significance value (p-value) of 0.017, which is significantly below the 0.05 alpha threshold, confirming a substantial difference in engagement levels between the active experimental class and the passive control class. The combination of academic tournaments and Talking Stick media proved effective in creating a fun, competitive, and focused classroom atmosphere, thereby significantly increasing student involvement dynamics. This study contributes to the field of pedagogy by providing empirical evidence that integrating collaborative game-based models with interactive media can effectively address student passivity and enhance learning motivation in religious education contexts.